2020
DOI: 10.1186/s12879-020-05241-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and antimicrobial resistance of group a streptococcus recovered from patients in Beijing, China

Abstract: Background: Group A streptococcus (GAS) is an important human pathogen responsible for a broad range of infections. Epidemiological surveillance has been crucial to detect changes in the geographical and temporal variation of the disease pattern. The objective of this study was to investigate the molecular epidemiological characteristics and antimicrobial resistance of GAS isolates from patients in Children's Hospital in Beijing. Methods: From 2016 to 2017, pharyngeal swab samples were collected from the outpa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 40 publications
3
10
0
Order By: Relevance
“…The Superantigen SpeA was found in 33.3% of this study and SpeA was 36.8% in the study of [5]. Also, this result is similar to [13] study which showed the percentage of SpeA gene was 34.34%. A study of [9] showed a lower percentage of SpeA (17.2%)…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The Superantigen SpeA was found in 33.3% of this study and SpeA was 36.8% in the study of [5]. Also, this result is similar to [13] study which showed the percentage of SpeA gene was 34.34%. A study of [9] showed a lower percentage of SpeA (17.2%)…”
Section: Discussionsupporting
confidence: 85%
“…Streptococcus pyogenes is sensitive to penicillin; different studies worldwide showed that like [10] study from Iran, [11] study from Senegal, [12] study from Ethiopia, [13] study from China and our study also showed that which confirms the penicillin is still the drug of choice for the treatment of GAS pharyngitis.…”
Section: Discussionsupporting
confidence: 76%
“…Ethiopia, [15] study from China and our study also showed that which confirm the penicillin is still the drug of choice for the treatment of GAS pharyngitis.…”
Section: Discussionsupporting
confidence: 74%
“…Many studies have found that antibiotics result in a higher DRP incidence than other drugs. This may be due to antibiotics, which can be used prophylactically, particularly for patients diagnosed with severe malnutrition, as these patients are at risk of developing infection even with a single microorganism 43 ; the absence of national prescribing guidelines and the prevalence of antibiotic resistance also contribute to the high levels of broad‐spectrum antibiotics prescribed in paediatric populations. 44 , 45 Many studies have shown that the high prevalence of DRPs may be attributed to the number of prescribed drugs.…”
Section: Discussionmentioning
confidence: 99%